Pembinaan Pemberdayaan Perempuan Pelaku Usaha Ganepo Melalui Legalitas Usaha Dan Inovasi Produk di Kampung Paluh Kecamatan Mempura Kabupaten Siak Provinsi Riau - Emilda Firdaus; Sukamarriko Andrikasmi; Firdaus Firdaus; Hengki Firmanda; Deby Kurnia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Women business actors processing cassava, especially ganepo products in Paluh Village do not yet have business legality and lack of product innovation, there is no business legality and no product innovation. Women entrepreneurs will find it difficult to expand their business network, and cannot penetrate the modern market, therefore it takes an empowerment that can improve the economy and social, and can create great women and independent villages. The purpose of community service activities that will be carried out is to provide knowledge and understanding of the importance of business legality and the need for product innovation so that later it can increase economic and social income and create jobs. The results of this community service are expected to have a good impact in terms of economic and social changes so that women can help the family economy and create an independent village community.